3D-printed bolus ensures the precise postmastectomy chest wall radiation therapy for breast cancer - Wang, Xiran; Zhao, Jianling; Xiang, Zhongzheng; Wang, Xuetao; Zeng, Yuanyuan; Luo, Ting; Yan, Xi; Zhang, Zhuang; Wang, Feng; Liu, Lei (Frontiers in Oncology, 2022)
Purpose：To investigate the values of 3D-printed bolus ensuring the precise postmastectomy chest wall radiation therapy for breast cancer. Methods and materials：The pre-clinical dosimetry and fitness evaluation of the 3D-printed bolus on the anthropomorphic phantom, the bolus was used for the postmastectomy radiotherapy. The dosimetric parameters of planning target volume (PTV) were assessed, including Dmin, Dmax, Dmean, D95%, homogeneity index (HI), conformity index (CI) and organs at risk (OARs). The absolute percentage differences (|%diff|) between the theory and fact skin dose were also estimated, and the follow-up was conducted for potential skin side effects. Results：In preclinical studies, 3D-printed bolus could better ensure the radiation coverage of PTV (HI 0.05, CI 99.91%), the dose accuracy (|%diff| 0.99%) and skin fitness (mean air gap 1.01mm). Of 27 eligible patients, we evaluated radiation dose parameter (median(min-max): Dmin 4967(4789-5099)cGy, Dmax 5447(5369-5589)cGy, Dmean 5236(5171-5323)cGy, D95% 5053(4936-5156)cGy, HI 0.07 (0.06-0.17) and CI 99.94% (97.41-100%)), assessed the dose of OARs (Ipsilateral lung: Dmean 1341(1208-1385)cGy, V5 48.06%(39.75-48.97%), V20 24.55%(21.58-26.93%), V30 18.40%(15.96-19.16%); Heart: Dmean 339(138-640) cGy, V30 1.10%(0-6.14%), V40 0.38%(0-4.39%); Spinal cord PRV: Dmax 639(389-898)cGy). The skin doses in-vivo were Dtheory 208.85(203.16-212.53)cGy, Dfact 209.53(204.14-214.42)cGy, |%diff| 1.77% (0.89-2.94%). 360 patients were enrolled in skin side effect follow-up study (including the above 27 patients), grade 1 was the most common toxicity (321, 89.2%), some of which progressing to grade 2 or grade 3 (32, 8.9% or 7, 1.9%), the radiotherapy interruption rate was 1.1%. Conclusion：3D-printed bolus could guarantee the precise radiation dose on skin surface, good fitness to skin, and controllable acute skin toxicity, which possesses a great clinical application value in postmastectomy chest call radiation therapy for breast cancer.